Incidencia de apectos historiográficos en la Organización de los saberes en la Universidad - Segundo, Rosa San; Codina Canet , Maria Adelina (Faculdade de Filosofia e Ciências, 2014)
Knowledge Organization has been generated primarily within universities. The university will establish that space which states and defines each knowledge and organizes all disciplines. It is necessary to address a genealogical and historical perspective of universities to analyze and identify the artificiality of our concepts, knowledge and classifications. The origin of the University dates back to the Middle Ages, the first University was in Córdoba, and how this institution influenced decisively in the knowledge that encouraged and organized themselves. In late Western Middle Ages, the organization of knowledge in universities is at the service of the Church. The modern world is going to separate the doctrine of the Church from University knowledge. And, subsequently, in various periods that there was a suppression of freedoms it has reversed immediately in the scientific content itself and in the bias that has characterized it. The construction and structuring of knowledge requires, as a fundamental value, a context of freedom. Globalization contributes to deconstruct organizations among knowledge while the technocratic discourse is imposed over other discourses and also over the critical capacity to develop global approaches. The university develops a performative discourse, that is the discourse itself producing the event to talk, words, language and classifications create reality. That is why scientific discourse is performative and shapes the knowledge itself. In the University context one must raise divergent approaches against existing systems and the dominant paradigms of thought. Thus the University has to fulfill a key role in stimulating critical thought. The University must pursue performing its tasks in freedom. What reports a fragility against the powers that seek to violate as it should have its own sovereignty. The University collects the accumulated knowledge and organizes it. It should question the order of knowledge and propose new models